Effects of medium-chain fatty acids on growth performance, microbial attributes, and fat deposition in broiler chicken - Ee, Hew Wei; Ramiah, Suriya Kumari; Mookiah, Saminathan; Idrus, Zulkifli (Czech Academy of Agricultural Sciences, 2024)
Poultry are monogastric animals that share a fat tissue structure that is strikingly comparable to the fat in animal feed. This indicates that the kind and source of fat in animal diets can significantly impact the accumulation and composition of fatty tissue in the resulting carcass. Hence, feeding (or dietary) manipulation is one of the best and commonly employed management strategies to improve of gut health and function in broiler production. Medium-chain fatty acids (MCFAs) are fatty acids with six to twelve carbon atoms that are prevalent in coconut and palm kernel oils. Much research is being conducted on nutritional approaches to enhance gut health and lower the usage of antibiotics in poultry farming. The use of MCFAs as an antibiotic substitute has been shown to have significant positive effects on broilers’ health and performance due mainly to their short pathways of absorption and oxidation. However, the fatty acid makeup of these feed additions may vary, and the results are sometimes inconsistent. Although supplementing hen diets with MCFAs can lower intermuscular and abdominal fat, the precise mechanics are not entirely understood. The distinct metabolic roles of fatty acids in chickens are linked to both the degree of saturation and the length of the chain. Detailed information on the effect of MCFAs on the growth performance, antimicrobial properties, and fat deposition in broiler chickens are summarised.